Takotsubo (stress) cardiomyopathy induced by acute asthma exacerbation in elderly woman - Khaled Al Khodari (21383186) (2023)
A 73‐year‐old patient who was admitted secondary to acute asthma exacerbation that required frequent salbutamol and adrenaline nebulization. Takotsubo cardiomyopathy (TTC) was diagnosed after the new onset of chest pain with modest troponin elevation and normal coronary angiogram. Low ejection fraction and apical akinesia were completely resolved after her symptoms got improved. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.7074